2022
DOI: 10.3390/cancers14071749
|View full text |Cite
|
Sign up to set email alerts
|

Elevated MACC1 Expression in Colorectal Cancer Is Driven by Chromosomal Instability and Is Associated with Molecular Subtype and Worse Patient Survival

Abstract: Metastasis-Associated in Colon Cancer 1 (MACC1) is a strong prognostic biomarker inducing proliferation, migration, invasiveness, and metastasis of cancer cells. The context of MACC1 dysregulation in cancers is, however, still poorly understood. Here, we investigated whether chromosomal instability and somatic copy number alterations (SCNA) frequently occurring in CRC contribute to MACC1 dysregulation, with prognostic and predictive impacts. Using the Oncotrack and Charité CRC cohorts of CRC patients, we showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…To further understand the CIN‐associated feature of the cells between epithelial cells with higher‐ and lower‐CNV, we analysed the differential expressed genes and found a total of 60 downregulated genes and 118 upregulated genes were identified in the epithelial cells with higher CNV higher (Figure S7C). The results showed that higher‐CNV cells expressed genes correlated with higher CIN such as TMEM173, 67 TP53/MDM2, 68 EGFR, 69 MACC1, 70 FOS, 70 UBAC2 71 (Figure 7H). These results indicated that epithelial cells with higher‐ and lower‐CNV exhibited higher and lower CIN.…”
Section: Resultsmentioning
confidence: 96%
“…To further understand the CIN‐associated feature of the cells between epithelial cells with higher‐ and lower‐CNV, we analysed the differential expressed genes and found a total of 60 downregulated genes and 118 upregulated genes were identified in the epithelial cells with higher CNV higher (Figure S7C). The results showed that higher‐CNV cells expressed genes correlated with higher CIN such as TMEM173, 67 TP53/MDM2, 68 EGFR, 69 MACC1, 70 FOS, 70 UBAC2 71 (Figure 7H). These results indicated that epithelial cells with higher‐ and lower‐CNV exhibited higher and lower CIN.…”
Section: Resultsmentioning
confidence: 96%
“…Identification of molecular subtypes in cancers contributes to more accurate prognostic assessment due to substantial phenotypic and molecular heterogeneity among patients, and simultaneously is an important basis for individualized therapy and precision medicine. Studies about molecular subtypes have been widely concerned with diverse cancer types, such as breast cancer [ 31 , 32 ], colon cancer [ 33 , 34 ] and gastric cancer [ 35 ], which provide potentially crucial data for diagnosis and treatment. In prostate cancer, via a comprehensive molecular analysis, seven major molecular subtypes are characterized by the Cancer Genome Atlas Research Network, TCGA-PRAD project [ 36 ], and relevant studies are also carried out to provide more data in cancer treatment [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%